A Historian in the Service of the Foreign Office: C. A. Macartney (1895-1978) and his writings on Hungary - Barta, Róbert (Acta Neerlandica, 2020)
This study is focusing on the life of C.A. Macartney as a diplomat and a historian especially on his writings on Hungary and the Hungarian history. The importance of this point goes back to the fact that he published a good number of books and articles on Hungary between the period of 1926 and 1978. It has been proved that this very rich publication activity of him basically influenced the attitudes of the English-speaking intellectual world towards Hungary and the Hungarians. In the life of Macartney the career as a diplomat and his so-called graphomaniac historian activity were closely connected. Although he was an expert of modern Hungarian history and worked for the British Foreign Office as a member of the Foreign Office Research Department (FORD) during WWII years, he also had a very well-grounded knowledge on the history of Austria and the Habsburg Empire. With his diplomatic activity and historical skill Macartney inspired generations of English-speaking historians, intellectuals and decision-makers in the subject of Hungary and the Hungarians. This fact well indicates the long-term importance and influence of C. A. Macartney as a pro-Hungarian historian and diplomat.